Life cycle assessment of open and closed hydroponic systems for vegetable (tomato and cucumber) production in arid lands - Eihab Fathelrahman; Raeda Osman; Sabeera Haris; Munjed Maraqa; Tamrat Gebiso; Berhanu Degefa; Elke Neumann; Dana Hoag (Journal of Cleaner Production, 2025)

Arbuscular mycorrhizal fungi travel the world with harvested underground crops - Ayesha Alam; Elke Gabriel-Neumann (Mycorrhiza, 2025)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Transport of nitrogen and zinc to rhodes grass by arbuscular mycorrhiza and roots as affected by different nitrogen sources (NH4 +-N and NO3 −-N) - Marie Franҫoise Seck-Mbengue; Anja Müller; Benard Ngwene; Elke Neumann; Eckhard George (Symbiosis, 2017)

Genetic kidney diseases: Caenorhabditis elegans as model system - Athina Ganner; Elke Neumann-Haefelin (Cell and Tissue Research, 2017)

Effects of single and mixed inoculation with two arbuscular mycorrhizal fungi in two different levels of phosphorus supply on β-carotene concentrations in sweet potato (Ipomoea batatas L.) tubers - Yu Tong; Elke Gabriel-Neumann; Benard Ngwene; Angelika Krumbein; Susanne Baldermann; Monika Schreiner; Eckhard George (Plant and Soil, 2013)

The symbiotic recapture of nitrogen from dead mycorrhizal and non-mycorrhizal roots of tomato plants - Anja Müller; Eckhard George; Elke Gabriel-Neumann (Plant and Soil, 2013)
Aims The aim was to quantify the nitrogen (N) transferred via the extra-radical mycelium of the arbuscular mycorrhizal fungus Glomus intraradices from both a dead host and a dead non-host donor root to a receiver tomato plant. The effect of a physical disruption of the soil containing donor plant roots and fungal mycelium on the effectiveness of N transfer was also examined. Methods The root systems of the donor (wild type tomato plants or the mycorrhiza-defective rmc mutant tomato) and the receiver plants were separated by a 30 μm mesh, penetrable by hyphae but not by the roots. Both donor genotypes produced a similar quantity of biomass and had a similar nutrient status. Two weeks after the supply of 15 N to a split-root part of donor plants, the shoots were removed to kill the plants. The quantity of N transferred from the dead roots into the receiver plants was measured after a further 2 weeks. Results Up to 10.6 % of donor-root 15 N was recovered in the receiver plants when inoculated with the arbuscular mycorrhizal fungus (AMF). The quantity of 15 N derived from the mycorrhizal wild type roots clearly exceeded that from the only weakly surface-colonised rmc roots. Hyphal length in the donor rmc root compartments was only about half that in the wild type compartments. The disruption of the soil led to a significantly increased AMF-mediated transfer of N to the receiver plants. Conclusions The transfer of N from dead roots can be enhanced by AMF, especially when the donor roots have been formerly colonised by AMF. The transfer can be further increased with higher hyphae length densities, and the present data also suggest that a direct link between receiver mycelium and internal fungal structures in dead roots may in addition facilitate N transfer. The mechanical disruption of soil containing dead roots may increase the subsequent availability of nutrients, thus promoting mycorrhizal N uptake. When associated with a living plant, the external mycelium of G. intraradices is readily able to re-establish itself in the soil following disruption and functions as a transfer vessel.

Root colonization by Piriformospora indica enhances grain yield in barley under diverse nutrient regimes by accelerating plant development - Beate Achatz; Sibylle von Rüden; Diana Andrade; Elke Neumann; Jörn Pons-Kühnemann; Karl-Heinz Kogel; Philipp Franken; Frank Waller (Plant and Soil, 2010)

Extraradical development and contribution to plant performance of an arbuscular mycorrhizal symbiosis exposed to complete or partial rootzone drying - Elke Neumann; Barbara Schmid; Volker Römheld; Eckhard George (Mycorrhiza, 2009)

Extraction of extraradical arbuscular mycorrhizal mycelium from compartments filled with soil and glass beads - Elke Neumann; Eckhard George (Mycorrhiza, 2005)

Colonisation with the arbuscular mycorrhizal fungus Glomus mosseae (Nicol. & Gerd.) enhanced phosphorus uptake from dry soil in Sorghum bicolor (L.) - Elke Neumann; Eckhard George (Plant and Soil, 2004)

Characterization of Porin from Roseobacter denitrificans - Uwe Neumann; Elke Maier; Emile Schiltz; Jürgen Weckesser; Roland Benz (Antonie van Leeuwenhoek, 1997)